1998
DOI: 10.1210/jcem.83.12.5471
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Mutation Screening of the Estrogen Receptor Beta Gene in Probands of Different Weight Extremes: Identification of Several Genetic Variants

Abstract: Estrogens are known to have an inhibitory effect on food intake in rodents and primates. Decreased estrogen levels that are found for instance in menopausal woman and in ovarectomized rodents result in body weight gain. Estrogen can act both in the periphery and in the central nervous system via at least two different estrogen receptors (alpha and beta). We systematically screened the coding region and part of the 5' and 3'regions of the estrogen receptor beta gene (ER beta) in 96 extremely obese children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(39 citation statements)
references
References 0 publications
2
36
1
Order By: Relevance
“…10 Two single nucleotide polymorphisms (SNPs) in this gene were described by Rosenkranz et al, 11 a RsaI restriction site at 1082G4A (a silent mutation in exon 5) and an AluI restriction site at 1730A4G (3' nontranslated region of the exon 8). The progesterone receptor gene is located on chromosome 11q22-23, 12 and Rowe et al 13 identified a 306-bp insertion of the PV/HS-1 Alu subfamily in intron 7, denominated PROGINS.…”
Section: Introductionmentioning
confidence: 99%
“…10 Two single nucleotide polymorphisms (SNPs) in this gene were described by Rosenkranz et al, 11 a RsaI restriction site at 1082G4A (a silent mutation in exon 5) and an AluI restriction site at 1730A4G (3' nontranslated region of the exon 8). The progesterone receptor gene is located on chromosome 11q22-23, 12 and Rowe et al 13 identified a 306-bp insertion of the PV/HS-1 Alu subfamily in intron 7, denominated PROGINS.…”
Section: Introductionmentioning
confidence: 99%
“…At the ESR2 locus the genotype of each individual was determined at a dinucleotide repeat 17 and two previously described SNPs (G1082A and A1730G) located in exon 5 and 8 respectively. 9 The distribution of the alleles at the dinucleoide repeat ESR1 in the control and AN populations is shown in Figure 1. Statistical analysis using the 'Clump' 19 computer package fails to show any signifi- cant difference in the distribution of alleles between the AN and control population ( 2 = 8.04, P Ͼ 0.2, df = 18).…”
mentioning
confidence: 99%
“…However the two SNPs studied at the ESR2 locus have previously been investigated in an AN population. 9 This study does not replicate the findings of Rosenkrantz et al 19 for suggestive evidence for association of the 1082G allele (nominal P value = 0.04) with AN, 8 conversely this study reports an association with the heterozygous genotype G1082A. The present study observed an increased frequency of the 1082A allele in the AN population ( 2 = 11.46, P = 0.0007, df = 1) which results in the genotype frequencies in this population alone deviating from Hardy-Weinberg equilibrium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The anorectic effects of estrogens have been noted for decades 46,47 and the estrogen receptor b (ERb) gene has shown associations with both AN and BN. 48,49 This gene is also located on chromosome 14, which was found to be in significant linkage with BN. 43 Interestingly, serotonin receptors are regulated by estrogen with estrogen affecting serotonin gene transcription.…”
Section: Int J Eat Disord 37 S43-s48 2005mentioning
confidence: 99%